Reduced lysosomal clearance of autophagosomes promotes survival and colonization of Helicobacter pylori. Issue 4 (28th February 2018) - Zhang, Lin; Hu, Wei; Cho, Chi H; Chan, Francis KL; Yu, Jun; Fitzgerald, J Ross; Cheung, Cynthia KY; Xiao, Zhan G; Shen, Jing; Li, Long F; Li, Ming X; Wu, Justin CY; et al.
Abstract: Evasion of autophagy is key for intracellular survival of bacteria in host cells, but its involvement in persistent infection by Helicobacter pylori, a bacterium identified to invade gastric epithelial cells, remains obscure. The aim of this study was to functionally characterize the role of autophagy in H. pylori infection. Autophagy was assayed in H. pylori ‐infected human gastric epithelium and the functional role of autophagy was determined via genetic or pharmacological ablation of autophagy in mouse and cell line models of H. pylori infection. Here, we showed that H. pylori inhibited lysosomal function and thereby promoted the accumulation of autophagosomes in gastric epithelial cells. Importantly, inhibiting autophagosome formation by pharmacological inhibitors or genetic ablation of BECN1 or ATG5 reduced H. pylori intracellular survival, whereas inhibition of lysosomal functions exerted an opposite effect. Further experiments demonstrated that H. pylori inhibited lysosomal acidification and the retrograde trafficking of mannose‐6‐phosphate receptors, both of which are known to positively regulate lysosomal function. We conclude that H. pylori subverts autophagy into a pro‐survival mechanism through inhibition of lysosomal clearance of autophagosomes. Disruption of autophagosome formation offers a novel strategy to reduce H. pylori colonization in human stomachs. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.